Acute myocardial infarction after inactivated COVID-19 vaccination: a case report and literature review - Ou, Weimei; Wang, Bin; Zhang, Guoming; Ding, Licheng; Liu, Zhixian; Wu, Kaimin; Sun, Guangfeng; Huang, Chengmin; Li, Zhaokai; Feng, Shuyuan; Gao, Rui (Frontiers in Cardiovascular Medicine, 2023)
A number of vaccines have been developed and deployed globally to restrain the spreading of the coronavirus disease 2019 (COVID-19). The adverse effect following vaccination is an important consideration. Acute myocardial infarction (AMI) is a kind of rare adverse event after COVID-19 vaccination. Herein, we present a case of an 83-year-old male who suffered cold sweat ten minutes after the first inactivated COVID-19 vaccination and AMI one day later. The emergency coronary angiography showed coronary thrombosis and underlying stenosis in his coronary artery. Type II Kounis syndrome might be a potential mechanism, which is manifested as coronary thrombosis secondary to allergic reactions in patients with underlying asymptomatic coronary heart disease. We also summarize the reported AMI cases post COVID-19 vaccination, as well as overview and discuss the proposed mechanisms of AMI after COVID-19 vaccination, thus providing insights for clinicians to be aware of the possibility of AMI following COVID-19 vaccination and potential underlying mechanisms.